2006
DOI: 10.1111/j.1939-1676.2006.tb00751.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Unilateral and Bilateral Deafness in Border Collies and Association with Phenotype

Abstract: Associations between CSD and pigmentation patterns linked to the merle gene were demonstrated for Border Collies. Evidence for an inherited component to CSD in Border Collies supports selective breeding from only tested and normal parents to reduce the prevalence of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
1
38
0
1
Order By: Relevance
“…Similarly, in a study in Border Collie puppies [11], the prevalence of CHSD was significantly higher in offspring from unilaterally deaf dams (10%) compared with those from normal hearing dams (2%). In contrast, there was no significant association between parental and offspring hearing status in Australian Cattle Dogs and Bull Terriers [1], although in that study, only a few subjects had parents of known hearing status [1].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Similarly, in a study in Border Collie puppies [11], the prevalence of CHSD was significantly higher in offspring from unilaterally deaf dams (10%) compared with those from normal hearing dams (2%). In contrast, there was no significant association between parental and offspring hearing status in Australian Cattle Dogs and Bull Terriers [1], although in that study, only a few subjects had parents of known hearing status [1].…”
Section: Discussionmentioning
confidence: 72%
“…The literature is divided as to the effects of sex on the prevalence of CHSD. In some studies, no association was observed between sex and CHSD in a variety of breeds [1,8,11]. This included a study in Australian Cattle Dogs that used both binary (ie deaf/not deaf) and ordinal (normal/unilateral/bilateral) outcome variables [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although useful, alternative data sources including referral practice data [51], [52], [53], pet insurance databases [27], official health schemes [54], [55], [56] and large scale questionnaire surveys [26], [57], [58], [59] are reported to suffer many limitations for the generation of prevalence values that can be generalised to the wider dog population. Analyses based on primary-care veterinary EPR data benefit from open-ended data collection allowing generation of stronger evidence from cohort compared with cross-sectional study designs [60], [61], [62].…”
Section: Discussionmentioning
confidence: 99%